Pengaruh Distributor Udara Pada Tungku Gasifikasi Updraft - Burhantoro, Jokor; , Subroto,ST,MT (2016)
This research aims to enhance the updraft gasification furnace performance by adding air distributor, in order to obtain better results, comparing the time to ignition, flame temperature and flame effectively. This study tested the performance waged updraft gasification furnace using air distributor. Each distributor has a pipe diameter of 30 mm and the diameter of the holes on the sides of 10 mm, the difference of each distributor is type 1 with a length of 200 mm number of holes 55, type 2 with a length of 400 mm number of holes 110 while type 3 with a length of 600 mm number of holes 165. The results showed that the furnace without distributor startup for 6 minutes at a temperature of 565°C, while the distributor type 1 startup 6 minutes degan temperature of 460°C, Type 2 startup 5 minutes with a temperature of 630°C, type 3 startup 4 minutes with a temperature of 576°C. The highest combustion temperatures without air distributor 790°C, with distributor type 1 incineration temperature 760°C, type 2 with a temperature of 861°C, and type 3 generate combustion temperature 907°C. Effectively without distributor flame lit for 23 minutes with distributor type 1 lit 21 minutes, type 2 for 20 minutes, type 3 for 19 minutes. Keywords: Gasification, distributor, updraft furnace, rice husks